Research on the Physics of Cancer 2016
DOI: 10.1142/9789814730266_0012
|View full text |Cite
|
Sign up to set email alerts
|

Potential Mechanisms of Cancer Prevention by Weight Control

Abstract: Weight control via dietary caloric restriction and/or physical activity has been demonstrated in animal models for cancer prevention. However, the underlying mechanisms are not fully understood. Body weight loss due to negative energy balance significantly reduces some metabolic growth factors and endocrinal hormones such as IGF-1, leptin, adiponectin, and glucocorticoids, etc., that may be associated with anti-cancer mechanisms. In this review, we summarized the recent studies related to weight control and gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…36,37 Our lab has shown that IGF-1 restoration within PE mice reversed the reduction of PI phospholipids and PI-associated PI3K. 23 Hence, it appears that IGF-1 is a key growth factor that promotes cancer development in overweight conditions, in part through promoting PI phosphorylation by PI3K and downstream Akt activity which contribute to anti-apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…36,37 Our lab has shown that IGF-1 restoration within PE mice reversed the reduction of PI phospholipids and PI-associated PI3K. 23 Hence, it appears that IGF-1 is a key growth factor that promotes cancer development in overweight conditions, in part through promoting PI phosphorylation by PI3K and downstream Akt activity which contribute to anti-apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a significant increase of both p53-transcripted IGFBP-3 and PTEN was found after treadmill exercise. IGFBP-3 is the most abundant IGF-1 binding protein that accounts for approximately 90% of bound IGF-1 in serum [ 35 ]. Increased expression of IGFBP-3 by exercise observed in this current study might be associated with less bioavailable IGF-1 as found in our previous studies [ 9 , 11 12 ].…”
Section: Discussionmentioning
confidence: 99%